The Influence of Reservation Agent Service Quality on Guest Room Booking Decisions at Jumeirah - Angel Vita Triana; Feri Ferdian (Pt. Threeple Herphi Educate, 2025)
This study investigates the influence of reservation agents’ service quality on guests’ booking decisions at Jumeirah Bali, a five-star luxury hotel facing increasing competition from online travel agencies (OTAs). Using a quantitative descriptive approach with a causal-associative design, data were collected from 100 respondents selected through purposive sampling, and analyzed using simple linear regression supported by validity, reliability, and classical assumption tests. The results reveal that service quality significantly affects booking decisions, with a regression coefficient of 0.618 and R² of 0.485, indicating that nearly half of the variance in guest decisions is explained by service quality. Politeness, professionalism, and product knowledge were identified as the strongest dimensions, while responsiveness and attentiveness, though satisfactory, require further improvement. These findings underscore the strategic role of reservation agents as the first service encounter that shapes guest perceptions, enhances direct booking performance, and strengthens long-term loyalty in a competitive hospitality market.